Coding and decoding of calcium signals in plants - Luan, Sheng (Springer eBooks., 2011)
Plants cannot move away from their environments. As a result, all plants that have survived to date have evolved sophisticated signaling mechanisms that allow them to perceive, respond, and adapt to constantly changing environmental conditions. Among the many cellular processes that respond to environmental changes, elevation of calcium levels is by far the most universal messenger that matches primary signals to cellular responses. Yet it remains unclear how calcium, a simple cation, translates so many different signals into distinct responses - how is the ?specificity? of signal-response coupling encoded within the calcium changes?